2018
DOI: 10.1039/c7dt04805j
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of chemical warfare agent simulants by air and moisture stable metal NHC complexes

Abstract: The cooperative effect of both NHC and metal centre has been found to destroy chemical warfare agent (CWA) simulants. Choice of both the metal and NHC is key to these transformations as simple, monodentate N-heterocyclic carbenes in combination with silver or vanadium can promote stoichiometric destruction, whilst bidentate, aryloxide-tethered NHC complexes of silver and alkali metals promote breakdown under mild heating. Iron-NHC complexes generated in situ are competent catalysts for the destruction of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 40 publications
0
16
0
3
Order By: Relevance
“…Research areas where metal mediated organic molecule transformations were conducted using bidentate NHC ligands to a lesser degree include reduction of carbonyl compounds using hydrosilylation process [ 209 , 214 , 215 , 216 , 217 , 218 , 219 ], isomerization of allylic alcohols [ 220 ], cross metathesis [ 221 ], arene borylation [ 222 , 223 ], amination [ 224 ], reduction of sulfoxides [ 225 ], alcohol oxidation [ 132 , 226 , 227 ], CO 2 reduction [ 228 , 229 , 230 , 231 ], norbornene polymerization [ 232 , 233 , 234 ], alkylation of amines [ 235 ], C-H borylation [ 236 ], CO 2 activation [ 237 ], hydroamination [ 238 ], functionalization of propane [ 239 , 240 ], ylide cycloaddition [ 74 ], three component coupling [ 241 ], hydroxylation of benzene [ 242 ], hydroaminoethlyation [ 243 ], water oxidation [ 244 ], amine alkylation [ 245 ], homopolymerization of ethylene [ 246 ], destruction of chemical warfare [ 247 ], Friedel-Crafts alkylation [ 248 ], C–H arylation [ 249 ], C–H oxidation [ 250 ], SABRE catalyst [ 251 ], and alcohol amidation reactions [ 211 ]. S...…”
Section: Synthesis and Applications Of Bidentate Ligands Bearing N-heterocyclic Carbenesmentioning
confidence: 99%
“…Research areas where metal mediated organic molecule transformations were conducted using bidentate NHC ligands to a lesser degree include reduction of carbonyl compounds using hydrosilylation process [ 209 , 214 , 215 , 216 , 217 , 218 , 219 ], isomerization of allylic alcohols [ 220 ], cross metathesis [ 221 ], arene borylation [ 222 , 223 ], amination [ 224 ], reduction of sulfoxides [ 225 ], alcohol oxidation [ 132 , 226 , 227 ], CO 2 reduction [ 228 , 229 , 230 , 231 ], norbornene polymerization [ 232 , 233 , 234 ], alkylation of amines [ 235 ], C-H borylation [ 236 ], CO 2 activation [ 237 ], hydroamination [ 238 ], functionalization of propane [ 239 , 240 ], ylide cycloaddition [ 74 ], three component coupling [ 241 ], hydroxylation of benzene [ 242 ], hydroaminoethlyation [ 243 ], water oxidation [ 244 ], amine alkylation [ 245 ], homopolymerization of ethylene [ 246 ], destruction of chemical warfare [ 247 ], Friedel-Crafts alkylation [ 248 ], C–H arylation [ 249 ], C–H oxidation [ 250 ], SABRE catalyst [ 251 ], and alcohol amidation reactions [ 211 ]. S...…”
Section: Synthesis and Applications Of Bidentate Ligands Bearing N-heterocyclic Carbenesmentioning
confidence: 99%
“…Recently, Arnold and co-workers reported that NHC-V(V) adducts 79, 80 and (ICy)VOCl3 were efficient stoichiometric reagents for the destruction of chemical warfare agent simulants (H agent and V agents) through cooperation of the V(V) metal center and the NHC ligand. 68 Thanks to NHC stabilization, Tavčar and coll. structurally characterized the first example of a [(L)VOF3] adduct (79b, Scheme 26).…”
Section: Scmentioning
confidence: 99%
“… 103 107 Beyond this, only a few other applications of vanadium-NHC complexes have been examined, including small molecule activation 108 , 109 and the neutralization of chemical warfare agents. 110 Still, most vanadium NHC complexes refer to diamagnetic vanadium(V) complexes, while low-valent vanadium complexes have been rarely investigated. 101 , 106 , 111 114 …”
Section: Introductionmentioning
confidence: 99%